Risk indicators for recurrent aphthous ulcers among adults in the US - Chattopadhyay A, Chatterjee S. (Blackwell Synergy, 2007)
Recurrent aphthous ulcers (RAU) in the oral cavity are painful, causing substantial morbidity in the US and elsewhere in the world.